Material and Resource Collaboration and Aiding an Aggressor State as Forms of Criminal Asset Circulation: Features of Criminal Offences and Problems of Qualification (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article is devoted to the study of the problem of distinguishing between criminal offences provided for in Part 4 of Article 111-1 and Article 111-2 of the Criminal Code of Ukraine. In order to improve the effectiveness of the application of criminal law, the need for a clear distinction between the elements provided for in Part 4 of Article 111-1 (regarding the transfer of material resources to illegal armed or paramilitary formations created in the temporarily occupied territory and/or to armed or paramilitary formations of the aggressor state) and Article 111-2 (in terms of the transfer of material resources or other assets to representatives of the aggressor state, its armed formations and/or the occupation administration of the aggressor state) of the Criminal Code of Ukraine. It is proposed to change the law enforcement concept: to qualify acts as collaboration (including material and resource collaboration) only if they are committed by a citizen of Ukraine under occupation or on the territory of the aggressor state.It has been proven that aiding an aggressor state constitutes a special manifestation of complicity in the crime of aggression. Providing assistance in waging an aggressive war harms not only national security, but also peace, the security of humanity and the international legal order. The expediency of excluding Article 111-2 from Section I of the Special Part of the Criminal Code of Ukraine and supplementing Section XX of the Special Part with a new article – Article 437-1 “Financing of the crime of aggression” – has been substantiated. The financing of the crime of aggression is proposed to be understood as the collection, storage or provision of any assets, directly or indirectly, for the purpose of their use or with the awareness of the possibility of their use, in whole or in part, for the planning, preparation, initiation and/or waging of an aggressive war. It is advisable to link the qualified types of this crime to the amount of assets collected, stored or provided to the aggressor state.